Analysis Of Constraints And Challenges In Optimizing Education And Facillities At The Multatuli Museum - Grace Netania Nauli Panjaitan; Roozana Maria Ritonga (JURNAL MANAJEMEN PENDIDIKAN, 2026)
The Multatuli Museum in Rangkasbitung is a historical museum that serves as a means of public education about Eduard Douwes Dekker, anti-colonial thought, and the history of Lebak Regency. In its implementation, the museum still faces various obstacles and challenges in optimizing the quality of education and facilities for visitors. The study, entitled "Analysis of Obstacles and Challenges of the Multatuli Anti-Colonialism Museum in Optimizing Education and Facilities in Rangkasbitung," aims to identify the obstacles, challenges, and efforts made by the museum in improving the quality of education and museum facilities. This study used qualitative methods with data collection techniques through interviews, observation, documentation, and literature studies. The research informants numbered six people consisting of the head of the museum, the Lebak Regency Culture and Tourism Office, educators, museum staff, and visitors. The results of the study indicate that the main obstacles include the limited number of educators, the less than optimal quality of educators, limited supporting facilities, suboptimal accessibility for people with disabilities, and limited space capacity. Efforts undertaken include revitalizing the museum, increasing the capacity of educators, and developing more friendly and comfortable facilities for visitors.